Serial assessment of pulmonary lesion volume by computed tomography allows survival prediction in invasive pulmonary aspergillosis - Vehreschild, Jörg Janne; Heußel, Claus Peter (European radiology, 2017)
BackgroundSerial chest CT is the standard of care to establish treatment success in invasive pulmonary aspergillosis (IPA). Data are lacking how response should be defined.MethodsDigital CT images from a clinical trial on treatment of IPA were re-evaluated and compared with available biomarkers. Total volume of pneumonia was added up after manual measurement of each lesion, followed by statistical analysis.ResultsOne-hundred and ninety CT scans and 309 follow-up datasets from 40 patients were available for analysis. Thirty-one were neutropenic. Baseline galactomannan (OR 4.06, 95%CI: 1.08-15.31) and lesion volume (OR 3.14, 95%CI: 0.73-13.52) were predictive of death. Lesion volume at d7 and trend between d7 and d14 were strong predictors of death (OR 20.01, 95%CI: 1.42-282.00 and OR 15.97, 95%CI: 1.62-157.32) and treatment being rated as unsuccessful (OR 4.75, 95%CI: 0.94-24.05 and OR 40.69, 95%CI: 2.55-649.03), which was confirmed by a Cox proportional hazards model using time-dependent covariates.ConclusionAny increase in CT lesion volume between day 7 and day 14 was a sensitive marker of a lethal outcome (>50%), supporting a CT rescan each one and 2 weeks after initial detection of IPA. The predictive value exceeded all other biomarkers. Further CT follow-up after response at day 14 was of low additional value. Key Points • CT evaluation offers good prediction of outcome for invasive pulmonary aspergillosis.• Predictive capability exceeds galactomannan, blood counts, and lesion count.• Any progression between day 7 and day 14 constitutes a high-risk scenario.
Gesehen am 25.09.2018